The efficacy and safety of bronchoscopy for treating transluminal broncholiths. (March 2021) - Wang, Hong; Zhang, Li; Li, Fangwei; Wan, Yixin
We aim to reveal the clinical features of transluminal broncholiths and to evaluate the efficacy and safety of bronchoscopy for treating transluminal broncholiths. Patients with transluminal broncholiths were enrolled in this retrospective study in Lanzhou University Second Hospital between January 2010 and December 2018. Then age, gender, symptoms, and signs, imaging characteristics, treatment methods, outcomes as well as complications were retrospectively analyzed. Twenty-eight patients with 36 pieces of transluminal broncholiths were diagnosed using chest CT and bronchoscopy, of which two patients underwent broncholiths removal via an elective surgical procedure and six patients were treated with one-time removal of broncholiths by bronchoscopy. Among the six patients who received one-time removal of stones by bronchoscopy, two underwent massive hemorrhage and one suffered from bronchial wall laceration in the process of broncholiths removal, all of the three patients received surgical treatment eventually. No serious complications occurred in the other 20 patients who underwent broncholiths removal via repeated bronchoscopy. Removal of transluminal broncholiths by bronchoscopy are effective and safe with less complications. When it is difficult to remove the transluminal broncholith completely at one time, repeated bronchoscopy could be chosen: First, to remove the portion which causes airway obstruction; and then to remove the remaining part by repeated bronchoscopy during the follow-up period. In case that severe distal lung tissue injury, massive hemoptysis or bronchial wall laceration occurs or the diagnosis of broncholiths is unclear, surgical treatment is required.